Distribution Law of In Situ Stress and Its Engineering Application in Rock Burst Control in Juye Mining Area - Guangchao Zhang; You Li; Xiangjun Meng; Guangzhe Tao; Lei Wang; Hanqing Guo; Chuanqi Zhu; Hao Zuo; Zhi Qu (Energies, 2022)
This paper presents an integrated approach for mathematical statistics, theoretical analysis, and a field test to investigate the distribution law of in-situ stress and its engineering practice of rock burst control. The test site is located in the Juye mining area, Shandong Province, China. The main conclusions included: (1) There are two types of in-situ stress states in the Juye mining area, σH > σV > σh (42.42%) and σH > σh > σV (57.57%), which are mainly caused by the tectonic stress of the Heze and Fushan faults (The σH, σV, and σh is the maximum principal stress, vertical principal stress or intermediate principal stress and minimum principal stress respectively). (2) The lateral pressure coefficients KH, Kh, and Kav show a non-linear distribution with increased depth, approaching 1.32, 0.96, and 1.41, respectively. The variation range of the horizontal difference stress μd is 0.09–0.58. (3) The average value of the stress gradient is 3.05 MPa/100 m, and the main directions of the maximum horizontal principal stress are northeast–southwest, and northwest–southeast. (4) A new combined supporting strategy, incorporating optimization of roadway layout, anti-impact support system design, and local reasonable pressure relief, was proposed for the rock burst control, and its validity was verified via field monitoring. All these design principles and support strategies for the rock burst control presented in this study can potentially be applied to other similar projects.